Knowledge management and organisational culture in higher education institutions - Doris Gomezelj Omerzel; Roberto Biloslavo; Aanita Trnavcevic (Journal for East European Management Studies, 2011)
This paper focuses on the higher education area in a small Central European country. Its purpose is to explore the concept of culture, the concept of knowledge management (KM) as well as the correlations among their dimensions at the university level. Since we assume that it is educational personnel who is involved in KM processes, our research covered the teaching staff. Our questionnaire is based on a similar research carried out by Wilkens et al. (2004). The literature is reviewed and the empirical analysis is performed in order to examine and to explain the relationship between organisational culture and knowledge management. The findings presented in the paper can be important for further development of the higher education sector in Central and Eastern European countries as well as for other profit oriented industries. – – Dieser Artikel beschäftigt sich mit dem Bereich der höheren Bildung in einem kleinen mitteleuropäischen Land. Ziel ist, die Konzepte von Kultur und Wissensmanagement, sowie die Zusammenhänge zwischen ihren Dimensionen auf der universitären Ebene zu untersuchen. Da wir der Meinung sind, dass der Wissensmanagementprozess im Bildungswesen besonders das Personal betrifft, fokussiert unsere Untersuchung auf das Lehrpersonal. Unser Fragebogen basiert auf einer ähnlichen Untersuchung von Wilkens et al. (2004). Neben einer Betrachtung der Literatur wird eine empirische Analyse durchgeführt, um die Beziehung zwischen Organisationskultur und Wissensmanagement zu untersuchen bzw. zu erläutern. Die Ergebnisse dieser Studie können für die weitere Entwicklung der höheren Bildung in Mittel- und Osteuropa wie auch für profitorientierte Organisationen bedeutsam sein.
Keywords: 650; knowledge management; organisational culture; higher education; knowledge; KM processes